“Perdidos de amor”?: relatos de assassinatos de mulheres em Goiânia (1970-1984) - Barros, Neide Célia Ferreira (2017)
This work will analyze criminal cases about murder of women killed by man, in Goiânia (1970-1984). And through them we will observe this relationships and powers between male and female gender in the capitol of Goiás, a frontier among a rural life and notions of modernity. This way, through Criminal Records of women went attacked by men, in a time of many changes, like feminist organizations, development of Brasilia and immigration to Goiânia, we will try to understand what means “be woman” and “be man” in this capitol, and what the consequences of this in their bodies, about theirs lifes and deaths, or protection and punition.